Development open source microcontroller based temperature data logger - M. H., Abdullah; S. A., Che Ghani; Z., Zaulkafilai; Saiful Nizam, Tajuddin (IOP Publishing Ltd, 2017)
This article discusses the development stages in designing, prototyping, testing and deploying a portable open source microcontroller based temperature data logger for use in rough industrial environment. The 5V powered prototype of data logger is equipped with open source Arduino microcontroller for integrating multiple thermocouple sensors with their module, secure digital (SD) card storage, liquid crystal display (LCD), real time clock and electronic enclosure made of acrylic. The program for the function of the datalogger is programmed so that 8 readings from the thermocouples can be acquired within 3 s interval and displayed on the LCD simultaneously. The recorded temperature readings at four different points on both hydrodistillation show similar profile pattern and highest yield of extracted oil was achieved on hydrodistillation 2 at 0.004%. From the obtained results, this study achieved the objective of developing an inexpensive, portable and robust eight channels temperature measuring module with capabilities to monitor and store real time data.